Registration and Labeling of Product Brands as an Effort to Increase Legal Awareness of Micro, Small, and Medium Enterprises in Majene Regency - Novitasari, Ika; Wulan, Retno; Anwar, Desi Amalia (Abdi Masyarakat, 2025)
This community service activity aims to increase legal awareness among Micro, Small, and Medium Enterprises (MSMEs) in Majene Regency through product brand registration and labeling. Based on local data, the majority of MSMEs have not registered their trademarks, making them vulnerable to piracy and difficult to penetrate the modern market. The program is implemented through five stages: observation, needs analysis, training, implementation, and evaluation. The training covers understanding trademark law, the importance of labeling, and technical assistance for trademark registration with the Directorate General of Intellectual Property Rights (DJKI). The results of the activity indicate an increase in MSMEs' knowledge and skills in legal protection of product identity and label quality, which impacts business competitiveness and sustainability. This activity also strengthens collaboration between academics, government, and the community in supporting the legality and professionalism of local MSMEs.